The urban improvise : improvisation-based design for hybrid cities - Kloeckl, Kristian (Yale University Press, 2020)
A book for architects, designers, planners, and urbanites that explores how cities can embrace improvisation to improve urban life The built environment in today's hybrid cities is changing radically. The pervasiveness of networked mobile and embedded devices has transformed a predominantly stable background for human activity into spaces that have a more fluid behavior. Based on their capability to sense, compute, and act in real time, urban spaces have the potential to go beyond planned behaviors and, instead, change and adapt dynamically. These interactions resemble improvisation in the performing arts, and this book offers a new improvisation-based framework for thinking about future cities. Kristian Kloeckl moves beyond the smart city concept by unlocking performativity, and specifically improvisation, as a new design approach and explores how city lights, buses, plazas, and other urban environments are capable of behavior beyond scripts. Drawing on research of digital cities and design theory, he makes improvisation useful and applicable to the condition of today's technology-imbued cities and proposes a new future for responsive urban design.